Savings and Liquidity Gluts and the American Long-Term Interest Rates Before the Great Financial Crisis - Parosa, Grzegorz (Journal of Public Governance, 2020)
Objectives: This article examines the impact of the global savings glut on the long-term interest rates in the United States before the Great Financial Crisis. It presents the impact mechanics of global savings on interest rates, discusses arguments supporting and contradicting the significance of this phenomenon, presents an alternative concept, namely global liquidity glut, and estimates the significance of both phenomena in shaping long-term interest rates in the USA before the crisis. Research Design & Methods: First, the impact of purchases of the US treasury bonds made by foreign investors on long-term interest rates is being assessed. Second, metrics representing global savings and liquidity gluts are being used to explain those purchases. Finally, a counterfactual exercise is used to reveal the impact that each of those factors had on the American ten-year treasury yields. Findings: The statistical analysis of both effects shows that foreign purchases of the Treasuries lowered the US longterm interest rates by up to 140 bps, with excess global savings depressing them by approximately 45 bps, and excess liquidity by another 75 bps. Implications / Recommendations: Monetary policy, as well as savings rates, might have wider than only local consequences. Excess liquidity and savings in one country can impact interest rates in other areas. Contribution / Value Added: This article presents an alternative and neglected in literature explanation for the phenomena of low long-term interest rates before the Great Financial Crisis in the USA, namely global liquidity glut that depressed interest rates more powerfully than excessive global savings, contributing to the development of the investment bubble on the housing market and, thus, the Great Financial Crisis.